CLUSTERING PENCAPAIAN TARGET PENJUALAN RUMAH PARA KARYAWAN MARKETING MENGGUNAKAN RAPID MINER DAN ALGORITMA K-MEANS - Muhammad Fahmi Julianto; Sofian Wira Hadi; Setiaji Setiaji; Windu Gata; Rangga Pebrianto (Bianglala Informatika, 2020)
In the competition of the business world today, we are required to always develop business in order to always be successful in competition. Fachry PropertyLand is one of the business fields engaged in the sale of homes. Everywhere this shop must meet the needs of customers who are currently trending. On Land Fachry Property Around the issue that always appears regarding sales. Where many employees do not meet their sales targets. Based on this, it is expected to facilitate the Land Fachry Property in assessing the appropriateness of its employees in determining employees who have met the target, has not met the target and does not meet the target, in the grouping process, the grouping method will be used using the K-Me Clustering Algorithm as a method of manual replacement and in its implementation the Data Mining software uses RapidMiner Studio version 9.2. With the application of Rapid Miner Studio, it is expected that the owner of Fachry Propertyland can see the results of the grouping that meets the target, does not meet the target and does not meet the target. It is expected that the owner of Fachry Propertyland can take action on these employees.